2012
DOI: 10.1111/nph.12043
|View full text |Cite
|
Sign up to set email alerts
|

The Brassica napus blackleg resistance gene LepR3 encodes a receptor‐like protein triggered by the Leptosphaeria maculans effector AVRLM1

Abstract: Summary LepR3, found in the Brassica napus cv ‘Surpass 400’, provides race‐specific resistance to the fungal pathogen Leptosphaeria maculans, which was overcome after great devastation in Australia in 2004. We investigated the LepR3 locus to identify the genetic basis of this resistance interaction. We employed a map‐based cloning strategy, exploiting collinearity with the Arabidopsis thaliana and Brassica rapa genomes to enrich the map and locate a candidate gene. We also investigated the interaction of Lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
256
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(258 citation statements)
references
References 77 publications
2
256
0
Order By: Relevance
“…With recent advances in Brassica genomics and understanding of the genetic basis of resistance against extracellular pathogens (i.e. B. napus resistance against Leptosphaeria maculans) (Larkan et al 2013(Larkan et al , 2015, rapid improvement in identifying novel sources of resistance against P. brassicae can be expected. Resistance genes mapped in previous studies can be further examined to characterise the genetic basis of resistance and they can be cloned.…”
Section: Resultsmentioning
confidence: 99%
“…With recent advances in Brassica genomics and understanding of the genetic basis of resistance against extracellular pathogens (i.e. B. napus resistance against Leptosphaeria maculans) (Larkan et al 2013(Larkan et al , 2015, rapid improvement in identifying novel sources of resistance against P. brassicae can be expected. Resistance genes mapped in previous studies can be further examined to characterise the genetic basis of resistance and they can be cloned.…”
Section: Resultsmentioning
confidence: 99%
“…For seedling resistance L. maculans has a gene for gene interaction with B. napus. Several resistance genes have been mapped, but only one, LepR3, has been cloned (Delourme et al 2006, van de Wouw et al 2009, Long et al 2011, Larkan et al 2013. Five avirulence genes have been cloned in L. maculans (AvrLm1, AvrLm4-7, AvrLm6, AvrLm11, AvrLmJ1) (Gout et al 2006, Parlange et al 2009, Balesdent et al 2013, van de Wouw et al 2014a).…”
Section: Blackleg Disease Of Canolamentioning
confidence: 99%
“…It has been demonstrated that SOBIR1 physically interacted with Cf-4, Ve1, LepR3, Rlm2, AtRLP1, AtRLP23, AtRLP30 and AtRLP42, and was required for the proper function of these RLPs. 9,10,12,13,15,16,[24][25][26] However, it is unclear about the biological relevance of the physical interaction between SOBIR1 and two developmental RLPs CLV2 and TMM, respectively. It could postulate that SOBIR1 may involve in the CLV2-and/or TMM-mediated developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…The RLP disease resistance genes include the tomato Cf and Ve genes that provide resistance against Cladosporium fulvum and Verticillium spp., respectively, 5,6 LeEIX genes that combat against the ethylene-inducing xylanase produced from Trichoderma biocontrol fungi, 7 apple HcrVf genes that confer resistance to the scab fungus Venturia inaequalis, 8 the LepR3 and Rlm2 genes that render race-specific resistance to the fungal pathogen Leptosphaeria maculans. 9,10 Genome-wide sequence analyses identified a total of 57 AtRLPs in Arabidopsis. 11,12 Although the biological functions of most AtRLP genes still remain unknown, a number of AtRLP genes have been assigned functions.…”
Section: Introductionmentioning
confidence: 99%